Gut microbiota of patients with post-stroke depression in Chinese population: a systematic review and meta-analysis - Li, Qiaoling; Zhang, Yuejuan; Wang, Xiaoqian; Dai, Lin; Zhao, Wenli (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEvidence of changes in the composition and function of the gut microbiota (GM) in post-stroke depression (PSD) patients is gradually accumulating. This study aimed to systematically evaluate the relationship between PSD and GM.MethodsWe searched in PubMed, Web of Science, Embase, Cochrane databases, Wangfang, VIP, CBM, and CNKI from the establishment of the database to April 17, 2024, and systematic review and meta-analysis were performed to investigate the differences of GM between patients with PSD spectrum and healthy controls (HC) or stroke spectrum.ResultThere were 14 studies consisting a total of 1,556 individuals included in the meta-analysis. The pooled results showed that PSD spectrum demonstrated significantly increased α diversity as indexed by Chao1 index, ACE indexes, Shannon index, and Simpson index as compared to HC. Additionally, stroke spectrum significantly increased α diversity as indexed by Simpson index compared to PSD. Furthermore, the pooled estimation of relative abundance showed that Bacteroidota, Fusobacteriota, and Pseudomonadota in PSD patients were significantly higher than those in the HC group, while the abundance of Bacillota was higher in the HC group. Moreover, significant differences in GM were observed between PSD patients and HC at the family and genus levels.ConclusionThis study found that the α diversity of PSD patients was higher than that of HC. Moreover, there were also differences in the distribution of GM at the phylum, family, and genus levels, respectively. At the same time, the level of Lachnospira in PSD patients was lower than that in the stroke group.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024582708.